PREPARATION AND EVALUATION OF TUSCAN SAUSAGE OF CHICKEN MEAT WITH THE ADDITION OF QUINOA - Rizzi, Gabrielli Zanini; Pereira, Thamie; de Souza, Edson Luiz; Soares, Fabiana Andreia A. S. M. (Anuário Pesquisa e Extensão Unoesc Videira, 2017)
The meat has exceptional organoleptic characteristics associated with its nutritional value, convert it into a food of animal origin most valued by consumers.  Due to the lack of time to eat properly, people started to consume more frequently, manufactured products, fried foods, sweets and sandwiches, disregarding the negative factors to health.  Aiming at the need to prepare food with low cholesterol levels, this study aimed to prepare and study the sensory acceptance of Tuscan sausage of chicken meat with the addition of quinoa. The practice of preparing formulations followed the standard procedure for the preparation of sausage from Tuscany using gut collagen and 3.0 % of quinoa. The samples were analyzed for protein (g 100g-1), fat (g100g-1), moisture content (g 100g-1), caloric value (kcal/g) and sensory analyses. The results of microbiological and physicochemical were within normal limits required by law, qualifying products made fit for human consumption.  A sensory acceptance test was carried out with 30 untrained panelists. The marks awarded by the panelists for the color, juiciness, odor flavor, texture and overall acceptance attributes were between 4 (Moderately Good) and 5 (Very Good), indicating that formulations are within the zone of acceptance. The marks awarded by the judges for the purchase of attitude corresponds to "Certainly Buy", showing that this product can be marketed.